2013
DOI: 10.1155/2013/209491
|View full text |Cite
|
Sign up to set email alerts
|

A Time Off Incentive Was Not Associated with Influenza Vaccination Acceptance among Healthcare Workers

Abstract: Objectives. The national influenza vaccination rate among healthcare workers (HCWs) remains low despite clear benefits to patients, coworkers, and families. We sought to evaluate formally the effect of a one-hour time off incentive on attitudes towards influenza vaccination during the 2011-2012 influenza season. Methods. All HCWs at the Philadelphia Veterans Affairs (VA) Medical Center were invited to complete an anonymous web-based survey. We described respondents' characteristics and attitudes toward influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
(16 reference statements)
0
6
0
Order By: Relevance
“…5,29,30,31 However, HCP acceptance of voluntary vaccination continues to be problematic. 32 Vaccination of HCP has previously been advocated as an effective means to control the spread of influenza and prevent absenteeism. [33][34][35] Absenteeism poses a threat to hospital effectiveness during influenza outbreaks when increased patient volume creates greater demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,29,30,31 However, HCP acceptance of voluntary vaccination continues to be problematic. 32 Vaccination of HCP has previously been advocated as an effective means to control the spread of influenza and prevent absenteeism. [33][34][35] Absenteeism poses a threat to hospital effectiveness during influenza outbreaks when increased patient volume creates greater demands.…”
Section: Discussionmentioning
confidence: 99%
“…Mandatory vaccination policies substantially increase rates of HCP vaccination 5 29 , 30 , 31 However, HCP acceptance of voluntary vaccination continues to be problematic 32 …”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of different kinds of PSL on increasing influenza vaccination coverage may be varied. One study found that modest incentives such as one-hour PTO did not improve the influenza vaccination rate among healthcare workers [19]. Another study concluded that universal PSL, which is more comparable to the PSL in the NHFS survey, resulted in greater than 40% higher odds of receiving seasonal influenza vaccination [18].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined the association between PSL and influenza vaccination uptake among U.S. workers. One study found that one-hour paid time off (PTO) did not improve the influenza vaccination rate among healthcare workers, while another study concluded that universal PSL resulted in a 42% higher odds of receiving seasonal influenza vaccination [19].…”
Section: Introductionmentioning
confidence: 99%
“…We identified a total of 26 articles that discussed incentives and vaccination, including vaccines for SARS-CoV-2 (12 studies) [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , hepatitis B (2 studies) [34] , [35] , HPV (2) [36] , [3] , maternal tetanus (3) [38] , [39] , [40] , influenza (5) [41] , [42] , [43] , adult tetanus, pneumococcus, and influenza (1) [46] , and a mix of different vaccinations (1) [47] . Target groups, if specified, included adolescents (2), students (2), elderly (2), health and social care workers (2), people with substance misuse disorders (1), and people who inject drugs (2).…”
Section: Resultsmentioning
confidence: 99%